Exploring the nexus between political careerism and political killings in South Africa’s local government level - Thandolwethu Nomarwayi; Mbasa Mvenene (Journal of Local Government Research and Innovation)
Background: In post-apartheid South Africa, much has been written about political killings or political assassinations, particularly at the local government level. Many studies carried out on this topic focus mostly on factionalism and internal squabbles within the African National Congress (ANC). Little attention has been paid to the impact of political careerism on political killings at the local government level.